FACTORS INFLUENCING COFFEE SHOP ENTREPRENEUR’ INTENTION USING SHOPEE PARTNER APPLICATION - Fitri Yutika (Jurnal Ekonomi, 2023)
Technological developments in marketing are a great opportunity for entrepreneurs to carry out business activities such as Coffee Shop. One of the innovations currently in development is Online Food Delivery service. ShopeeFood is an online food delivery service that connects buyers with food and beverage sellers through the Shopee Partner application. This study aims to determine the factors that influence the intention of Coffee Shop entrepreneurs using Shopee Partner application with Unified Theory of Acceptance and Use of Technology (UTAUT) theory. The research was conducted to 50 Coffee Shops in Pontianak City by distributing questionnaires. Data were analyzed using the Structural Equation Modeling method with SmartPLS software. The results of the study show that Effort Expectancy and Facilitating Conditions have a significant influence on shaping of Coffee Shop entrepreneurs' intentions to adopt the Shopee Partner application. It shows that Coffee Shop entrepreneurs in Pontianak City prioritize the level of ease of using Shopee Partner application and other supporting resources. Performance Expectancy and Social Influence variables did not affect the intentions of Coffee Shop entrepreneurs as they do not view digital transformation as an opportunity that provides benefits and less responsive to social factors that used and need online food delivery services.